Professional burnout in primary health care workers of the Republic of Kazakhstan - Lyudmila Migina; Ayan Myssayev; Serik Meirmanov; Assem Uristemova (Elsevier, 2023)
Background/objectives: Emotional exhaustion is the most common feature of overall burnout among primary care physicians. The purpose of our study is to identify professional burnout among doctors and nurses of the highest level. Methods: The data were obtained using a social survey of doctors and nurses in primary health care organizations. Using the MBI questionnaire. The study locations were medical centers in urban and rural areas in eight regions of Kazakhstan. A total of 612 urban and 244 rural primary health care workers took part. Results: Mean score ±standard deviation on the exhaustion subscale was 32.6 ± 13.5, on the depersonalization subscale - 14.4 ± 6.1, on the personal achievement subscale - 42.2 ± 7.5. Overall, the high prevalence of emotional exhaustion, depersonalization, and personal achievement was 57.4%, 64.6%, and 65.0%, respectively. Statistically significant predictors for emotional burnout were such as the location of work, urban or rural (OR = 1.973; p < 0.050, as well as who the employee was a doctor or nurse (OR = 2.137 p < 0.001). Work for a quieter job was a significant factor for personal achievement (OR = 4.709 p < 0.016), (OR = 9.341 p < 0.001), respectively. Statistically significant predictors for depersonalization was the status of the employee, namely, whether his work was permanent or not full -time (OR = 1.542 p < 0.001). Gender (OR = 0.350 p < 0.018), job location urban or rural (OR = 1.918 p < 0.050), and alcohol consumption (OR = 4.493 p < 0.021) were statistically significant for personal achievement. Conclusion: Mental and psychological health issues have become an increasingly important research topic in recent years. In our study, more than half of the study population reported professional burnout, namely exhaustion, depersonalization, and lack of personal achievement. We found a statistically significant relationship between emotional exhaustion and job location, as well as employee status, Depersonalization, and employee status and position. Personal achievements and gender with work location. To change my job to a more calm one was in all three parameters. Doctors have higher emotional exhaustion than nurses.